Machine Learning and Knowledge Discovery in Databases European Conference, ECML PKDD 2014, Nancy, France, September 15-19, 2014. Proceedings, Part I - Calders, Toon; Esposito, Floriana; Hüllermeier, Eyke; Meo, Rosa (Lecture Notes in Artificial Intelligence, 2014)
This three-volume set LNAI 8724, 8725 and 8726 constitutes the refereed proceedings of the European Conference on Machine Learning and Knowledge Discovery in Databases: ECML PKDD 2014, held in Nancy, France, in September 2014. The 115 revised research papers presented together with 13 demo track papers, 10 nectar track papers, 8 PhD track papers, and 9 invited talks were carefully reviewed and selected from 550 submissions. The papers cover the latest high-quality interdisciplinary research results in all areas related to machine learning and knowledge discovery in databases.